Evaluation of Breast Animation Deformity following Pre- and Subpectoral Direct-to-Implant Breast Reconstruction: A Randomized Controlled Trial - Dyrberg, Diana L.; Bille, Camilla; Koudahl, Vibeke; Gerke, Oke; Sørensen, Jens A.; Thomsen, Jørn B. (Archives of Plastic Surgery, 2022)
Background The incidence of breast animation deformity (BAD) is reported to be substantial after direct-to-implant breast reconstruction with subpectoral implant placement. It has, however, never been examined if BAD can occur following prepectoral implant placement. Our primary aim was to compare the incidence and degree of BAD after direct-to-implant breast reconstruction using either subpectoral or prepectoral implant placement. Secondary aim of this study was to assess and compare the level of pain between sub- and prepectoral reconstructed women.Methods In this randomized controlled trial, patients were allocated to reconstruction by either subpectoral or prepectoral implant placement in accordance with the CONSORT guidelines. The degree of BAD was assessed by the “Nipple, Surrounding skin, Entire breast (NSE)” grading scale 12 months after surgery. The level of postoperative pain was assessed on a numerical pain rating scale.Results We found a significant difference in the degree of BAD favoring patients in the prepectoral group (23.8 vs. 100%, p < 0.0001; mean NSE grading scale score: 0.4 vs. 3.6, p < 0.0001). The subpectoral reconstructed group reported higher levels of pain on the three subsequent days after surgery. No significant difference in pain levels could be found at 3 months postoperatively.Conclusion The incidence and degree of BAD was significantly lower in women reconstructed by prepectoral direct-to-implant breast reconstruction. Unexpectedly, we found mild degrees of BAD in the prepectoral group. When assessing BAD, distortion can be challenging to discern from rippling.
Keywords: breast reconstruction; breast deformity; breast implant; treatment outcome; incidence